2015
DOI: 10.1016/j.jacc.2015.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Oxidized Phospholipids on Apolipoprotein B-100 to Cardiovascular Outcomes in Patients Treated With Intensive Versus Moderate Atorvastatin Therapy

Abstract: BACKGROUND Oxidized phospholipids on apolipoprotein B-100 (OxPL-apoB) is a biomarker of increased risk for major adverse cardiovascular events (MACE) in community cohorts, but its role in patients with stable coronary heart disease (CHD) is unknown. OBJECTIVES We sought to examine the relationship of these oxidative biomarkers to cardiovascular outcomes in patients with established CHD. METHODS In a random sample from the Treating to New Targets trial, OxPL-apoB levels were measured in 1,503 patients at ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…As described previously in both humans and nonhuman primates, our data show that cynomolgus monkeys had highly variable hepatic mRNA expression levels ( 44,45 ). Results from this events, lending evidence that the content of pro-infl ammatory OxPLs are key determinants of atherogenic risk mediated by Lp(a) (37)(38)(39)(40)(41)(42).…”
Section: Pharmacology Of Isis-apo(a) Rx In Lean Cynomolgus Monkeyssupporting
confidence: 81%
“…As described previously in both humans and nonhuman primates, our data show that cynomolgus monkeys had highly variable hepatic mRNA expression levels ( 44,45 ). Results from this events, lending evidence that the content of pro-infl ammatory OxPLs are key determinants of atherogenic risk mediated by Lp(a) (37)(38)(39)(40)(41)(42).…”
Section: Pharmacology Of Isis-apo(a) Rx In Lean Cynomolgus Monkeyssupporting
confidence: 81%
“…This increased circulating OxPL content in subjects with elevated Lp(a) suggests that a comparable impact of OxPL may hold true in vivo . In support, we have previously shown that OxPL-apoB levels were potent predictors of progressive atherosclerosis as well as the risk of cardiovascular disease and death in patients 1416,46 .…”
Section: Discussionsupporting
confidence: 75%
“…Because each mole of OxPL has 1 PC headgroup recognized by E06, this can be reported as nM PC-OxPL, as previously described for measurement of OxPL on apolipoprotein B-100 (OxPL-apoB). (13),(14), (15),(16) We present the OxPL-PLG data as both RLU and nM PCOxPL to facilitate comparison with prior work.…”
Section: Methodsmentioning
confidence: 99%